Relação entre os elementos definidores da síndrome metabólica e a função tireoidiana em indivíduos com eutireoidismo da população de Fortaleza-CE - Castelo, Maria Helane Costa Gurgel (2010)
The association between clinically overt thyroid dysfunction and the development of metabolic disorders is well established. However, in recent years, the debate about the relationship between changes in thyroid function (TF), the metabolic syndrome (MS) or its components has gained special attention. Since the thyroid stimulating hormone (TSH) screening test more sensitive for detecting changes in TF, has been discussed more stringent criteria of normality in healthy individuals, from the finding of an association of adverse clinical outcomes with values previously considered normal. However, it is difficult to define "health", particularly in relation to body adiposity, whereas obesity is a condition of high prevalence itself linked to numerous illnesses. This study aimed to evaluate the relationship between the defining elements of MS and changes in the TF and determine the reference value (RV) of TSH in a sample of healthy subjects, from the stand point of thyroid, in the city of Fortaleza, Brazil. This is a cross-sectional study conducted from March 2009 to January 2010 which included 267 euthyroid subjects were selected from clinical and laboratory criteria. This team comprised four stages including the completion of a self-administered questionnaire, laboratorial and medical evaluation, with anthropometry, measurement of waist circumference (WC), systolic blood pressure (SBP) and diastolic (DBP), determination of serum TSH, free thyroxine ( FT4), triiodothyronine (T3), anti-thyroperoxidase (ATPO), thyroglobulin antibody (ATG), fasting glucose (FG), insulin, total cholesterol (TC), LDL, HDL and triglycerides (TG), insulin resistance calculated by homeostasis model assessment (HOMA-IR ), and the realization of thyroid ultrasound (TUS). Among the 267, 125 participants were selected, named individuals-reference, characterized by normal FT4, anti-thyroid antibody negative and normal TUS normal. This group composed the database of individual records necessary for determining the VR TSH according to the NCCLS and NACB guidelines. Data were subjected to statistical analysis (software Statistical Package for the Social Sciences (SPSS), versão 14.0 para Windows) being used the Student t test, Mann-Whitney test to compare continuous variables, the chi-square test for categorical variables and Spearman test for correlation analysis, adopting the statistical significance level of 5% (p < 0.05). Multiple linear regression models were applied to evaluate the associations between the FT with the concentrations of serum lipids and various traits of MS, with and without adjustment for age, sex, and HOMA-IR. To determine the reference range of TSH were adopted percentiles 2.5% and 97.5% of the distribution curve of the analyte, as the correspondents of the lower and upper limits of TSH RV. After the analysis, we observed that 77.2% of euthyroid subjects had at least one defining element of MS. Regarding the relationships between metabolic parameters and FT, there was positive correlation of TSH with only WC and DBP, while the FT4 correlated inversely with four (WC, FG, TG, DBP) in the five defining elements of MS. Yet been demonstrated a clear inverse correlation between the status of TF and HOMA-IR. From these findings, we speculate that in fact there is an association between the TF and MS, and that serum levels of thyroid hormones (THs) more than TSH, are related to cardiovascular risk factors. In determining the reference range of TSH, the values are between 0.56 to 4.45 mIU / l, which is in line with the points previously established in population-based studies.